PERANAN BEKRAF DALAM MENDORONG EKSPOR PRODUK EKONOMI KREATIF DI PASAR GLOBAL - Hasna Wijayati, Halifa Haqqi & (Transformasi, 2018)
Cultural and Creative Industries (CCIs) shows a significant increase, both globally and locally. The market for creative industries in Global Market is wide open. For Indonesia, the creative industry sector is also a leading sector. This potential continues to be maximized by the Indonesian government with the establishment of the Badan Ekonomi Kreatif (Bekraf) as a non-ministerial institution that focuses on managing the creative economy sector in 2015. The study aims to determine Bekraf's role in encouraging the export of creative economic products to the global market. This study uses qualitative methods with literature study. Conclusion of this research, regarding the role of Bekraf in efforts to increase exports of Indonesia's creative economy include: (1) mapping the potential of Indonesia's creative economy; (2) promotion assistance abroad; (3) Human Resources competency improvement programs and utilization of digital technology.Keywords : creative industry, Europe market, export.